Critical Airway Team: A Retrospective Study of an Airway Response System in a Pediatric Hospital. (December 2017) - Sterrett, Emily C.; Myer, Charles M.; Oehler, Jennifer; Das, Bobby; Kerrey, Benjamin T.
Objective: Study the performance of a pediatric critical airway response team. Study Design: Case series with chart review. Setting: Freestanding academic children's hospital. Subjects and Methods: A structured review of the electronic medical record was conducted for all activations of the critical airway team. Characteristics of the activations and patients are reported using descriptive statistics. Activation of the critical airway team occurred 196 times in 46 months (March 2012 to December 2015); complete data were available for 162 activations (83%). For 49 activations (30%), patients had diagnoses associated with difficult intubation; 45 (28%) had a history of difficult laryngoscopy. Results: Activation occurred at least 4 times per month on average (vs 3 per month for hospital-wide codes). The most common reasons for team activation were anticipated difficult intubation (45%) or failed intubation attempt (20%). For 79% of activations, the team performed an airway procedure, most commonly direct laryngoscopy and tracheal intubation. Bronchoscopy was performed in 47% of activations. Surgical airway rescue was attempted 4 times. Cardiopulmonary resuscitation occurred in 41 activations (25%). Twenty-nine patients died during or following team activation (18%), including 10 deaths associated with the critical airway event. Conclusion: Critical airway team activation occurred at least once per week on average. Direct laryngoscopy, tracheal intubation, and bronchoscopic procedures were performed frequently; surgical airway rescue was rare. Most patients had existing risk factors for difficult intubation. Given our rate of serious morbidity and mortality, primary prevention of critical airway events will be a focus of future efforts.